Dampak Lingkungan Kerja dan Stress Kerja Terhadap Performa Pegawai - L, Riska Gebiyanti; Andi Sapada, Achmad Faisal; Hartati, Hartati; Lukman, Siti Diva Syarifah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study aims to analyze the influence of the work environment and work stress on employee performance at the Sidrap Religious Court. The results show that the work environment partially has a negative influence on employee performance, while work stress simultaneously has a positive and significant influence on employee performance